Implementasi Customer Development Model dalam Pengembangan Produk Baru Bisnis Kuliner: Studi pada Pantaco Bites - Cherilda Luqia Nurintan; Pratami Wulan Tresna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to apply the Customer Development Model (CDM) in the development of new products for the culinary business Pantaco Bites, which offers pancake tacos with a healthy, practical, and aesthetic concept. The research uses a mixed methods approach, which includes a quantitative approach through Likert scale surveys and the Customer Satisfaction Index (CSI), as well as a qualitative approach through observation and in-depth interviews. Data were collected through four stages of the CDM: customer discovery, customer validation, business creation, and company building. Target customers were selected through purposive sampling. The research results indicate that CDM is effective in identifying customer needs, verifying products through direct feedback, and creating added value that aligns with the target market's lifestyle. The CSI results show a high level of customer satisfaction, with customers appreciating the quality, practicality, and aesthetics of the products. These results emphasize the importance of combining quantitative and qualitative analysis to understand market preferences and evaluate the business strategies being used. In short, the implementation of CDM provides businesses with a competitive advantage by enabling more focused product development that aligns with customer needs. To enhance competitiveness in the culinary industry, this research suggests optimizing digital marketing strategies, educating consumers about product benefits, and applying CDM to other market segments.